Pharmacokinetic evaluation of twice-a-week micafungin for prophylaxis of invasive fungal disease in children with acute lymphoblastic leukaemia: a prospective observational cohort study. (22nd December 2021) - Bury, Didi; Wolfs, Tom F W; ter Heine, Rob; Muilwijk, Eline W; Tissing, Wim J E; Brüggemann, Roger J
Abstract: Objectives: To determine the pharmacokinetics of twice-a-week micafungin prophylaxis in paediatric leukaemic patients to provide the rationale for this approach. Methods: Twice-a-week micafungin at a dose of 9 mg/kg (maximum 300 mg) was given during the leukaemic induction treatment with at least one pharmacokinetic assessment. Non-linear mixed-effects modelling was used for analysis. For model building, our paediatric data were strengthened with existing adult data. Monte Carlo simulations were performed with twice-a-week dosing regimens of 5, 7 and 9 mg/kg and flat dosing per weight band. Simulated paediatric exposures were compared with the exposure in adults after a once-daily 100 mg regimen. Results: Sixty-one paediatric patients were included with a median age and weight of 4.0 years (range 1.0–17) and 19.5 kg (range 8.60–182), respectively. A two-compartment model best fitted the data. CL and central V d were lower ( P  < 0.01) in paediatric patients compared with adults. Predicted exposures (AUC0–168 h ) for the 5, 7 and 9 mg/kg and flat dosing per weight band regimens exceeded the adult reference exposure. Conclusions: All twice-a-week regimens appeared to result in adequate exposure for Candida therapy, with simulated exposures well above the adult reference exposure. These findings provide the rationale for the pharmacokinetic equivalence of twice-a-week and once-daily micafungin regimens. The greater micafungin exposures seem to be caused by a slower-than-anticipated CL in our paediatric leukaemic patients. The generalizability of our results for Aspergillus prophylaxis cannot be provided without assumptions on target concentrations and within-class identical efficacy.